The use of imazamethabenz (AC 222 293, assert) for wild oat (Avena fatua) control in cereals of the Western Cape - Van Zyl, Willem Albertus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1991.